Management of oral late sequelae in head and neck cancer long-term survivor awaiting re-irradiation: Case report and literature review - Macedo, Larissa Fernanda dos Santos Lima; Siqueira, Juliana Mota; Gonçales, Luara Maria Cerioni; Gallo, Camila de Barros; Domaneschi, Carina (Journal of Oral Diagnosis, 2020)
Head and Neck Squamous Cell Carcinoma (HNSCC) constitute more than 90% of the head and neck cancer cases, often presenting as a locally advanced disease. As techniques are improving, life expectancy of HNSCC patients have risen overtime, leading to a larger number of people facing late sequelae that often culminate in a direct and significant impact on their quality of life. For those individuals, recurrence may represent a concern for curative attempts and overall survival rates. This paper reports a clinical case of a long-term HNSCC survivor who developed multiple oral sequelae from previous cancer treatment and recent second malignancies; in order to proceed for re-irradiation, she was referred for oral assessment. Due to her age and comorbidities, private professionals reportedly refused to provide oral care, causing an immense delay to her oncology treatment that led to the progression of diverse oral symptoms and cancer itself. Considering the urgency of head and neck re-RT, the outlined oral treatment plan was conservative and included scaling and root planing, oral prophylaxis, direct resin composite restorations and hygiene orientation, in a single session. She was also referred for low-level lasertherapy. Afterwards, her health had deteriorated to such a stage she did not qualify to actually proceed for re-RT, and instead was treated with end-of-life care until the time of her death, 8 months after the above-mentioned appointments. The authors believe the prolonged search for proper oral care was significant to her already poor prognosis, as it caused an immense delay to the start of the cancer treatment.